Women on boards and women in management - Elín Blöndal 1966-; Bendixen, Jytte Kaltoft (2012)
Equal participation of men and women in management and on boards of private and public companies, has in the past years been high on the political agenda in the Nordic countries and in the EU. ICELAND has in 2010 chosen the legislative path and included equal quotas. In DENMARK the government policy was until recently not to legislate on this matter concerning private companies. Instead of legislation the government preferred softer measures. However with the change of government in autumn 2011 this policy changed, and the Social Democratic led government in May 2012 has introduced legislation, however without proposing quotas on boards. This paper gives a comparative overview of the legislation as adopted in Iceland and the recent proposal for legislation in Denmark. Further it also includes a comparative overview of the soft measures that has been used in the two countries. On this background will be identified some similarities and differences in the regulation in the two countries and also some areas for possible inspiration and learning.